HIV among people who inject drugs in Central and Eastern Europe and Central Asia: a systematic review with implications for policy. Issue 5 (18th October 2012) - Jolley, Emma; Rhodes, Tim; Platt, Lucy; Hope, Vivian; Latypov, Alisher; Donoghoe, Martin; Wilson, David
Abstract : Background and objectives: HIV among people who inject drugs (PWID) is a major public health concern in Eastern and Central Europe and Central Asia. HIV transmission in this group is growing and over 27 000 HIV cases were diagnosed among PWID in 2010 alone. The objective of this systematic review was to examine risk factors associated with HIV prevalence among PWID in Central and Eastern Europe and Central Asia and to describe the response to HIV in this population and the policy environments in which they live. Design: A systematic review of peer-reviewed and grey literature addressing HIV prevalence and risk factors for HIV prevalence among PWID and a synthesis of key resources describing the response to HIV in this population. We used a comprehensive search strategy across multiple electronic databases to collect original research papers addressing HIV prevalence and risk factors among PWID since 2005. We summarised the extent of key harm reduction interventions, and using a simple index of 'enabling' environment described the policy environments in which they are implemented. Studies reviewed: Of the 5644 research papers identified from electronic databases and 40 documents collected from our grey literature search, 70 documents provided unique estimates of HIV and 14 provided multivariate risk factors for HIV among PWID. Results: HIV prevalence varies widely, with generally low or medium (<5%) prevalence in Central Europe and high (>10%) prevalence in Eastern Europe. We found evidence for a number of structural factors associated with HIV including gender, socio-economic position and contact with law enforcement agencies. Conclusions: The HIV epidemic among PWID in the region is varied, with the greatest burden generally in Eastern Europe. Data suggest that the current response to HIV among PWID is insufficient, and hindered by multiple environmental barriers including restricted access to services and unsupportive policy or social environments.